Karst Water Pressure’s Varying Rule and Its Response to Overlying Strata Movement in Coal Mine - Jian Hao; Hua Bian; Anfa Chen; Jiahui Lin; Dongjing Xu (Advances in Civil Engineering)
Karst water is widespread throughout China and is heavily influenced by complex geological conditions, and floor inrush of karst waters associated with coal seams is the second most common coal mine disaster in China. Due to the limitation of precision and cost of geophysical exploration technology, the volume and pressure of karst water are challenging to measure, especially during the mining process. Therefore, predicting karst pressure’s response to mining is critical for determining the mechanism of water inrush. Here, closed karst water pressure (CKWP) response to mining was studied in an innovative physical simulation experiment. In the simulation experiment, a capsule and a pipe were designed to reflect CKWP and the water level. In the experiment, the vertical stress and karst water level were monitored throughout the process of an advancing coal panel. Monitoring results show that the range of the abutment pressure was about 40 cm, and the peak coefficient value was about 2. When the working face is far away from the water capsule, the stress and water column near the water capsule have no obvious change. With the working face 10 cm from the water capsule, the stress and water column height increased significantly. When the working face was right above the water capsule, the stress and water column rose sharply and reached the maximum value. When the working face advanced beyond the water capsule, the stress and water column height declined. Through establishing a structural mechanics model, the karst water system underneath the working face is assumed to be a hydraulic press. Accordingly, the compressed area was assumed to be a piston. The karst water pressure increases sharply, while the piston is compressed, increasing water inrush risk. This discovery may help determine the water inrush mechanism from a novel point of view.